THE ROLE OF MEMORIAL GARDEN AND PARK COMPLEXES IN THE PRESERVATION OF CULTURAL AND HISTORICAL HERITAGE - Lysuchevska, Maryna; Kosyk, Oksana (Theory and practice of design, 2023)
The article provides an overview of Ukrainian and world memorial parks, defines their functionality and impact on modern society. Their role, history, and architectural features are considered. It is found that memorial garden and park complexes influence the formation of historical memory, consciousness and dissemination of cultural values. It is outlined that they are important elements of cultural heritage and harmonious development of modern society. The article shows the importance of these objects for preserving the memory of tragic events and natural disasters, and for informing the population about socially important issues of our time. The purpose of the study is to analyse the impact and significance of memorial garden and park complexes as a mechanism for preserving cultural and historical values, promoting their study and reproduction in the collective memory of society. The research methodology is based on the analysis of literary sources, archival materials, and expert assessments. The results of the analysis show that memorial garden and park complexes play an important role in the preservation and promotion of cultural and historical heritage, providing access to valuable objects for the general public. They are not only places of storage of artefacts of past eras, but also centres of education, cultural and educational work and tourism development. The scientific novelty lies in the identification of the key role played by memorial garden and park complexes in the preservation and promotion of cultural heritage, as well as in proposals for improving their effectiveness in preserving historical values. Memorial garden and park complexes play a key role in preserving and maintaining cultural and historical heritage. Their significance lies in the fact that they are not only places of recreation, but also carriers of memory, which is reflected in the landscape, architecture, sculpture and many elements that tell the story. Memorial gardens and parks contribute to the preservation of historical facts, traditions, cultural values and the nation’s heritage, expand educational opportunities and promote tourism. They become important centres that reflect the country’s rich heritage and serve as a place for patriotic education and cultural exchange. The practical significance of the article lies in the development of recommendations for improving the efficiency of management of memorial garden and park complexes aimed at preserving and promoting cultural and historical heritage, which will contribute to the further development of the cultural and artistic environment and tourist potential of the regions.